Prevalence and factors associated with Shoulder Complex Function (SCF) among the elderly in private physiotherapy clinic in Klang Valley, Malaysia - Yin, Nina Lim Siang; Shahar, Hayati Kadir; Asmuri, Siti Noraini binti (Universiti Putra Malaysia Press, 2024)
Introduction: Shoulder problems have been a challenge among the aging population. Although reports surfaced on factors affecting shoulder dysfunction, however, such studies in relation to other factors like neck pain (NP) factor are limited especially among the elderly in the urban population. This study investigated the prevalence and factors associated with shoulder complex dysfunction among the outpatient elderly attending private physiotherapy clinics. Methods: A total of 75 elderly aged ≥ 60 years old from four private physiotherapy clinics were recruited by simple random sampling method. The elderly were evaluated using the QuickDASH questionnaire to assess shoulder complex dysfunctions and NP scale. Results: A total of 92 of participants have shoulder complex dysfunction. A positive correlation of NP to shoulder complex dysfunction (r (75) = 0.83, p<.001) with significant associations of sex (z= -2.549, p=0.011), smoking (z= -2.388, p=0.017), lifestyle (z= -5.780, p=0.000), hypertension (z= -2.808, p=0.005), osteoarthritis (z= -2.966, p=0.003), and NP scale (z= -2.173, p=0.031). The predicting factor of shoulder complex dysfunction is sex (β = 0.156, t (74) = 2.240, p= 0.028) and NP scale (β = 0.704, t (74) = 7.853, p= 0.000). Conclusion: There is a high prevalence of shoulder complex dysfunction among the outpatient elderly attending private physiotherapy clinics with a predicting associating factor of sex and NP.